Immunohistochemical Analysis of BRAF (V600E) Mutation and P16 Expression in Malignant Melanoma in Lagos, Nigeria: A 10-Year Retrospective Study - O. Obadofin; K. Badmos; N. Orsi; M. Bipin; O. Rotimi; A. Banjo (Journal of Skin Cancer)
Background. In Blacks, malignant melanoma (MM) is associated with greater morbidity and mortality compared to Caucasians. MMs with BRAF V600E mutation as well as those with loss of p16 protein expression are associated with aggressive behavior and worse prognosis. Objectives. We determined BRAF (V600E) mutation status and loss of p16 expression in MM cases in Lagos, Nigeria, and correlated these with histopathologic parameters and patients’ age. Methods. Forty-five cases of MM received between January 2005 and December 2014 in the Anatomic and Molecular Pathology Department of Lagos University Teaching Hospital were subjected to immunohistochemical studies to determine BRAF V600E mutation and p16 protein expression. These included cutaneous (n=37), musosal (n=3), and ocular MM (n=2) as well as lymph node metastatases (n=3). Results. BRAF (V600E) mutations were detected in 5/45 (11%) while 31/45 (69%) of the cases had loss of p16 expression. No statistically significant association was found between the BRAF (V600E) mutation, loss of p16 expression, and histologic parameters such as histologic variant, Clark level, Breslow thickness, and ulceration. Conclusion. BRAF (V600E) mutation was detected only in a small proportion of cases while loss of p16 expression occurred in most cases which also had high Clark level, high Breslow thickness, and ulceration.